Bacteriological Profile and Predictors of Death Among Neonates With Blood Culture-Proven Sepsis in a National Hospital in Tanzania—A Retrospective Cohort Study - Ba-alwi, Nour Abdallah; Aremu, John Ogooluwa; Ntim, Michael; Takam, Russel; Msuya, Mwanaidi Amiri; Nassor, Hamid; Ji, Hong (Frontiers in Pediatrics, 2022)
Background Neonatal sepsis is still a major cause of death and morbidity in newborns all over the world. Despite substantial developments in diagnosis, treatments, and prevention strategies, sepsis remains a common problem in clinical practice, particularly in low-resource countries. Methods A retrospective cohort study of 238 neonates with positive blood culture-proven sepsis (in Muhimbili National Hospital) from January 2019 to December 2020. The outcomes of hospitalization were survival and death. Results 45.38% mortality resulted from 238 neonates who had sepsis exclusively based on blood culture positivity. A significant association was found between very low birth weight (VLBW), hyperglycemia, mechanical ventilation, and high neonatal mortality. Among the different clinical presentations of neonatal sepsis, lethargy, vomiting, and respiratory distress were found to be frequently associated with neonatal mortality. Furthermore, Sepsis with Gram-negative bacteria, and early-onset sepsis were also associated with high neonatal mortality. Of the 108 neonatal deaths, the largest proportion (40%) was observed with Staphylococcus, the remaining 38% were caused by Klebsiella, 14% by E. coli, 5% by Pseudomonas, 4% by Acinetobacter, and 2% by Streptococcus. No neonatal deaths from Serratia infection were observed. The overall resistance of isolated organisms to the recommended first-line antibiotics for cloxacillin was 100%, 82.5% for ampicillin, and 71.3% for gentamicin. The resistance pattern for the recommended second-line antibiotics was 75.9% for ceftriaxone, 35.9% for vancomycin, and 17.5 % for amikacin. Conclusion VLBW, early-onset sepsis, clinical and laboratory parameters like lethargy, vomiting, and hyperglycemia, sepsis with gram-negative bacteria, and being on mechanical ventilation are strong predictors of death in neonatal sepsis. In addition, this study discovered extraordinarily high resistance to conventional antibiotics. These findings give light on crucial aspects to consider in preventing this disease and poor outcomes.